Collaborative Governance dalam Pengembangan UMKM Pasca Covid-19 di Kabupaten Bogor - Ramadhany, Oemmy; Ariestha, Bethra; Asropi, Asropi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The business structure in Bogor Regency, according to Online Single Submission (OSS) data, is dominated by Micro, Small and Medium Enterprises (MSMEs). This should provide quite a large opportunity to increase the contribution of Gross Regional Domestic Product (GRDP) in West Java. However, the contribution of MSMEs in Bogor Regency to GRDP is still lower than that of MSMEs in Bekasi Regency, Bandung City, and Karawang Regency, which have fewer MSMEs than Bogor Regency. This research aims to identify traditional collaborations that have been carried out and plan collaborative action strategies that can be implemented by the Bogor Regency Government. The research method used by the author is a qualitative approach. The qualitative approach places more emphasis on observing phenomena that exist in the research subject, namely the collaborative governance strategy of Bogor Regency MSMEs. Data was collected through in-depth interviews and literature studies. The findings from this research are that there has been no evaluation regarding the effectiveness of traditional forms of cooperation in developing MSMEs in Bogor Regency. Collaborative governance in the development of post-COVID-19 MSMEs in Bogor Regency can be carried out through the Ansell & Gash stage approach, which involves government, private, community, and academic stakeholders.